Efficient desalination method using a subsurface drainage pipe with rice husk in paddy fields - Jia, Ziyi; Terasaki, Hiroaki; Fukuhara, Teruyuki; Zhou, Beibei (Geoderma Regional, 2023)
The 2011 tsunami from the Great East Japan Earthquake caused severe soil salinization in agricultural lands. Soil salt removal using a subsurface drainage pipe with rice husk has been widely used in many paddy fields. However, desalination was frequently decided based on the expertise of construction contractors in Japan resulting in inefficient desalination methods that led to a significant wastage of freshwater resources and a long duration for agricultural restoration. Previous studies have either simulated conventional subsurface drainage without considering the rice husk zone or focused only on rice husk subsurface drainage systems excluding pipes. However, no quantitative research on a subsurface drainage pipe with rice husk has been conducted using numerical simulations. Accordingly, this study proposes highly efficient desalination methods for reducing freshwater wastage using an indoor experiment and numerical simulation. The indoor experiment of the subsurface drainage pipe with rice husk was set up in a soil tank of 900 × 200 × 900 mm (length × width × height), with reproduced salinization using NaCl solution inundation and soil desalination using freshwater. Thereafter, calibration and validation using HYDRUS-2D confirmed the model's accuracy in reproducing the movement of water and salt in the soil profile. The effects at a ponding water depth of 50–300 mm under various conditions on desalination efficiency and leaching water quantity were simulated. The results suggested that as the same desalination effect is achieved, low ponding water depths with multiple desalting cycles will reduce the quantity of leaching water. Moreover, under low ponding water depth conditions, prolonging the flooding duration will cause a decrease in the desalination effect. In addition, for the same quantity of leaching water, increasing the pipe burial depth is more beneficial to desalination than expanding the rice husk zone width. This study provides theoretical guidance for water conservation and high-efficiency desalination using the subsurface drainage pipe with rice husk for post-disaster early restoration of paddy fields. •Multiple desalting cycles at low water depth are beneficial for water conservation•Early restoration of farmland with high water depth and few cycles of desalination•Prolonging flooding duration with low water depth decreased drained salt mass•Desalination efficiency decreased for a ponding water depth of <108 mm•Increasing pipe burial depth and rice husk zone width can improve desalting effect